DAYA TERIMA MASYARAKAT PADA SELAI WANI (MANGIFERA CAESIA) SEBAGAI DIVERSIFIKASI PANGAN - Ida Bagus Satria Harta Widana; Risa Panti Ariani; Cokorda Istri Raka Marsiti (Universitas Pendidikan Ganesha, 2026)
Wani fruit (Mangifera caesia) is a seasonal fruit endemic to Bali with high nutritional and economic value. However, its postharvest shelf life is relatively short, lasting only 4–5 days after ripening, which often results in significant postharvest losses. This study aimed to: (1) develop a formulation for wani fruit jam based on the literature on tropical fruit jam processing, and (2) evaluate consumer acceptability of the jam in terms of color, aroma, taste, and texture. The study employed a laboratory experimental method using a One-Shot Case Study design. The research object was wani fruit jam formulated with 400 g of fruit pulp, 60 g of granulated sugar, 100 mL of water, and 10 g of lemon juice. The formulation was developed through preliminary trials and standard tropical fruit jam ratios. The study involved 50 untrained panelists, consisting of students from Universitas Pendidikan Ganesha, who evaluated the product using a five-point hedonic scale. Data were analyzed using descriptive quantitative methods by calculating the mean score for each sensory attribute. The results indicated that the wani fruit jam achieved a